Performance analysis of a novel combined cooling, heating and power system based on carbon dioxide energy storage. (15th May 2019) - Liu, Zhan; Cao, Feng; Guo, Jianzhang; Liu, Jie; Zhai, Hongyan; Duan, Zhenya
Highlights: A novel trigeneration system using carbon dioxide as working fluid is examined. Energy efficiency can be larger than 1 with the decrease of hot fluid reutilization. This trigeneration system is more suitable for heating users than cooling users. The maximum energy efficiency can be optimized by regulating throttle valve 1. Abstract: Carbon dioxide has been proposed as a new working fluid in energy storage system since compressed air energy storage technology is restricted in application by geological formations. Besides, combined cooling, heating and power system can supply diversified energies to users. A novel trigeneration system based on transcritical Brayton cycle and carbon dioxide energy storage is thus presented in this work. The operating principle of this system is described and thermodynamic model is developed for numerical analysis of the system performance. Meanwhile, parametric analysis is conducted to examine the effect of key parameters on system performance. Results indicate that a lower hot fluid reutilization ratio is beneficial for improving cooling ability, heating ability and total output energy, and this trigeneration system is much more suitable for heating users than cooling users. The operational range and cooling range of system is slightly influenced by storage pressure, but are broaden by the increase of pressure difference through first throttle valve and ambient temperature. The cooling ability and heating ability increase monotonically with storage pressure, and decrease with pressure difference through first throttle valve and ambient temperature.